Enhancing academic adjustment, motivation and life satisfaction of female preparatory students using acceptance and commitment therapy - Moges Asale; Shimeles Ayalew; Belay Kibret (College of education, Bahir Dar University, 2023)
Academic motivation, adjustment, and life satisfaction are among the most important factors that have a great impact on students' success at school and well-being in life which are highly determined by psychological flexibility. Acceptance and commitment therapy (ACT), which is a mindfulness-based therapy, is believed to impact students' psychological flexibility. The aim of this study was to investigate the effectiveness of ACT group intervention on academic achievement motivation, adjustment, and life satisfaction of students. A program that consisted of 10 weekly sessions, each of which took two hours in duration was implemented for 45 grade 11 female students at Bole Preparatory School following The Melbourne Clinic ACT group treatment procedure. Participants were recruited based on their response to the call for participation, assessment through intake interview and confirmed availability to attend the intervention sessions. The participants were randomly assigned into two groups: intervention (treatment) group (ACT) and the waitlist (control) group (WLG). Both baseline (pre-test) and end line (post-test) were conducted. Adjustment Inventory for School Students (AISS), Deo and Mohan Achievement Motivation (DMAM), Acceptance and Action Questionnaire (AAQ II), Cognitive Fusion Questionnaire (CFQ), The Mindful Attention and Awareness Scale (MAAS), Valued Living Questionnaire (VLQ) and Satisfaction with Life as a Whole and Personal Wellbeing Index Scale (PWI) were used to measure psychological flexibility academic adjustment, academic motivation, satisfaction with life, and personal wellbeing. A repeated measure ANOVA model was used to test the hypothesis. The results showed that students in the ACT group reported greater academic motivation, adjustments, life satisfaction and psychological flexibility than those in the WLG after receiving the 10-weeks long standard ACT group intervention. Based on the findings of this study, it can be concluded that ACT group intervention can help to boost achievement motivation, adjustment, and satisfaction in life among female high school students.